Assessment of Hand-Hygiene Practices Among Health Care Workers at Kisoro Hospital, Kisoro District. - Nsenga, Alex (2023)
According to WHO, (2017), annual report, 70% of the hospital acquired infections can be averted by the practice of hand hygiene (HH) which is a systematic procedure of cleansing hands using soap and water or using antiseptic hand rub for removal of transient microorganism from hands. Purpose of the study: The main purpose of the study was to assess the hand hygiene practices among health care workers at Kisoro hospital in Kisoro District in order to contribute to the control of poor hygiene related diseases. Specific objectives of the study were; to examine the level of knowledge of health workers on hand-hygiene practice, to determine the level of adherence to hand-hygiene practice among health workers and to identify key barriers m implementation of hand-hygiene practice among health workers at Kisoro hospital in Kisoro District. Study design: The study employed a cross-sectional, descriptive study design usmg both qualitative and quantitative methods of data collection. Findings of the study: A total of 106 health care workers were involved in the study as study respondents. The study findings revealed that 91(85.8%) of the respondents had good knowledge about hand hygiene. 83 (96.7%) of the respondents had high awareness in respect to practice of hand washing before touching a patient and lowest awareness in respect to practice of hand hygiene after exposure to immediate surroundings of a patient. Regarding knowledge on commonly used agents in hand hygiene, the study revealed that the biggest number of respondents was using water and soap 63(60%) for hand hygiene. Level of adherence to hand hygiene practices was at 57%. However, 91(85.8%) of the respondents reported lack of continuous flow of water as the major barrier hindering health care workers from practicing hand hygiene. Conclusion: The study concluded that most of the health workers know the meaning of hand hygiene and five moments of hand hygiene but the actual practice of hand hygiene is still a big challenge Recommendation: The study recommended that, refresher trainings/CMEs' for health care workers on hand hygiene including socio-behavioral change communication should be organized by the Ministry of health through the District health department to increase awareness among health care workers about the importance of hand hygiene and change a negative attitude of health care workers towards hand hygiene practice. The study also recommended that; there is need for proper quantification of hand hygiene items such as hand sanitizers, gloves, soap by the hospital management in order to avoid stock outs and while ordering for hospital supplies such items should be given priority since hand hygiene is one of the most important ways to reduce the prevalence of hospital acquired infections. Keywords: Assessment, Hand-Hygiene Practices, Health Care Workers, Hospital, Kisoro District.